Stroke: Management and prevention - Montagu, A; Reckless, I; Buchan, A (2012)
Cerebrovascular disease can be devastating for patients and their families. However, there is much that can be done to attenuate cerebral damage and reduce the extent of any disability. Active intervention is best seen in three phases: acute therapy, rehabilitation and secondary prevention. Thrombolysis within 4.5 hours of symptom onset substantially reduces morbidity from ischaemic stroke. Administration requires the use of clear protocols to triage, transport and investigate patients without delay. The concept of a 'chain of survival' for 'acute brain attack' is paramount. Computed tomography remains an appropriate imaging technique in the early assessment of most stroke patients. An organized approach to stroke care, provided in a specialist environment, reduces disability and saves lives. Such care has many components and it is not known which specific elements confer benefit. Adoption of a 'care bundle' approach including the active management of pyrexia and hyperglycaemia, and early screening for swallowing difficulties has been shown to be beneficial. Secondary prevention should be considered in all patients presenting with stroke and transient ischaemic attack. Validated tools have been developed for the estimation of recurrence risk in the individual. Assessment of the carotid arteries should be carried out urgently as the efficacy of surgical endarterectomy falls with time. Anticoagulant therapy for those with atrial fibrillation is safer in the elderly population with atrial fibrillation than is often assumed.